Dos conjuntos habitacionais aos arranha-céus: um estudo sobre o impacto da urbanização na orla de Olinda (1970-1985). - Mozdzenski Junior, Sergio Luiz Carvalho (2023)
The population increase in the city of Olinda, after the 1960s, reflected in numerous urban and social transformations in the daily lives of residents. As an example, the anthropic actions that took place on the edge of the city, which led to the widening of roads, to receive a greater flow of vehicles, as well as the verticalization of the landscape, with the construction of skyscrapers, to house new residents, as a result of the growing real estate speculation in the region, especially in the neighborhoods of Casa Caiada and Rio Doce. Thus, based on the relationship between history and images, we aimed to produce an e-book with photographs of the Olinda waterfront, between the years 1970 and 1985, the main period of this most abrupt phase of transitions, analyzing records of images captured at the time, which allow us to understand the urban, social and cultural aspects, and at the same time, the landscape alteration of that space. Our theoretical axis enters Cultural History, supported by researchers who analyze images and the study of cities, such as Ana Maria Mauad, Boris Kossoy, Peter Burke, Sandra Pesavento e Virgínia Pontual. The methodology was based on an iconographic analysis of photographs that are available at the Municipal Public Archive of Olinda Antonino Guimarães, Joaquim Nabuco Foundation, among others.